The ImpactoftheRedScareof1920sonImmigrants - Hammia, Belkhir; Selmi, Hichem (University of Eloued جامعة الوادي, 2024)
The United States’ history is a pact with social events that affected the lives and rights of American civilians and their government , whether positivelyor negatively. Between the period of 1919 and 1920, there has been a notable rise in the number of immigrants that followed communist, socialist ,and anarchist ideologies, due to the 1917s Russian October revolutionand the anarchist bombingin the UnitedStates,in other words, thisgenerated what was called The Red Scare. The aim of the studyistoinvestigate theimpact of theRed Scare on immigrants inthe UnitedStates duringthe 1920s.It was carried out in order to clarify and inform about the struggle that immigrants encountered in the USA during the period of WWI. Starting with the extent to which the immigrants were targeted during the Red Scare, investigating the socioeconomic repercussions of discrimination on immigrant communities, including employment, housing and social integration, andinvestigatingthe role ofthe government policies inaffecting theirlives andassessing the impact of these policiesoncommunitydynamics andlastlyprovidinginsightsintotheir experiences, challengesand copingmechanisms. This research was conducted in qualitative approach based on historical, and descriptive methods, using demographic and case studies, predicting their expected outcomes. This research contributes to a nuanced understanding of the Red Scare's impact on immigrants, shedding light on a historical period that has lasting implications for immigration policies andsocietal attitudes.The findings reveal significant socioeconomicrepercussions forimmigrant communities,including discriminationinemployment,housing,andsocial integration.
Literature and Civilization
Keywords: Immigrants; Impact; RedScareofthe1920s; UnitedStates